Creating Immersive Audio in a Historical Soundscape Context - Ferreira, Carolina Ribeiro Dias (2022)
A soundscape is the representation of an acoustic environment in a specific context and time. Soundscapes evolve over time according to the changes in social, cultural and political contexts, and they constitute a unique way of experiencing auditory memories of a specific period in history. Considering that the soundscape of a place is ever-changing and it can provide us with important information about a location’s context in time, the study and preservation of soundscapes, in particular historic soundscapes, has gained relevance in the cultural heritage protection and promotion process. Soundscapes enrich the history of places and contribute to enhance the visitors experience in tourism contexts. However, it is impossible to go back in time and record the acoustic experiences from centuries ago. For that reason, the closest we can get to experience an historic soundscape is by trying to recreate it. This can be done with the support of historic documentation and audio immersion technology. We created a solution that allows users to construct scenes that provide immersive auditory experiences. The immersive audio files generated are obtained by combining different current sound recordings, and by composing an immersive auditory scene that can be recorded by the user. Here, we propose Immerscape, a tool that non-expert users can easily use to create immersive historical soundscapes. This work was validated by a user study that evaluated the tool’s functionalities and its acceptance by users. The proposed work is a contribution to the PASEV project, whose main purpose is to preserve and promote Évora’s rich cultural heritage, in particular, their historic soundscapes corresponding to the period between 1540 and 1910.